2008
DOI: 10.1128/jvi.00656-08
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2-Mediated Phosphorylation of Small Hepatitis Delta Antigen at Serine 177 Enhances Hepatitis Delta Virus Antigenomic RNA Replication

Abstract: The small hepatitis delta virus (HDV) antigen (SHDAg) plays an essential role in HDV RNA double-rollingcircle replication. Several posttranslational modifications (PTMs) of HDAgs, including phosphorylation, acetylation, and methylation, have been characterized. Among the PTMs, the serine 177 residue of SHDAg is a phosphorylation site, and its mutation preferentially abolishes HDV RNA replication from antigenomic RNA to genomic RNA. Using coimmunoprecipitation analysis, the cellular kinases extracellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Thr 178 is part of the well conserved P-E-T/S-P motif and only found in the hinge domain of ␤-arrestin-2 (Fig. 5, A and B) (27,28). Replacing Thr 178 for an Ala residue abolished the effect of PD98059 treatment on the receptor/␤-arrestin-2 complex half-life (Fig.…”
Section: Mapk Regulates B2r/␤-arrestin-2 Complexes In Endosomes Andmentioning
confidence: 96%
“…Thr 178 is part of the well conserved P-E-T/S-P motif and only found in the hinge domain of ␤-arrestin-2 (Fig. 5, A and B) (27,28). Replacing Thr 178 for an Ala residue abolished the effect of PD98059 treatment on the receptor/␤-arrestin-2 complex half-life (Fig.…”
Section: Mapk Regulates B2r/␤-arrestin-2 Complexes In Endosomes Andmentioning
confidence: 96%
“…Phosphorylation [32,33], acetylation [34], methylation [35], prenylation [36] and several other post translational modifications of the HD antigens [37][38][39] have been shown to orchestrate the life cycle of the virus. Different phosphorylation patterns of the small and large HD-Ag account for their distinct biological functions [32] and phosphorilated SHD-Ag increases replication from antigenomic to genomic RNA [33].…”
Section: Progress In Hdv Virologymentioning
confidence: 99%
“…Different phosphorylation patterns of the small and large HD-Ag account for their distinct biological functions [32] and phosphorilated SHD-Ag increases replication from antigenomic to genomic RNA [33]. Acetylation and deacetylation of HD-Ag may provide a molecular switch for the synthesis of the different RNA species [34], and interactions with the multifunctional transcription factor YY1 and its associated acetyltransferase selectively modulates replication of the genomic and antigenomic forms [39].…”
Section: Progress In Hdv Virologymentioning
confidence: 99%
“…Our previous studies revealed that a Ser 177 mutant of SHDAg lost the ability to interact with RNAP II and to support HDV replication from antigenomic to genomic RNA. Moreover, we found that extracellular signal-regulated kinase 1/2 (ERK1/2) is an SHDAgassociated kinase, and that its activation enhances the phosphorylation levels of Ser 177 of SHDAg and the antigenomic RNA replication of HDV in vivo (11,52). However, the role of SHDAg phosphorylation in regulating HDV antigenomic RNA replication remains unclear.…”
mentioning
confidence: 86%
“…Our previous studies revealed that SHDAg is a phosphorylated protein, and that Ser 177 is the residue that is phosphorylated predominantly (52,54). In addition, the S177A SHDAg mutant (replacement of Ser 177 with Ala 177 ) exhibits the disruption of the synthesis of HDV genomic RNA with the preservation of the synthesis of antigenomic RNA (11,52) (pSer 177 -HDAg) specifically. 293T cells were transfected with HDV-expressing plasmids that were either antigenomic RNA replication competent (2AGwt) or replication deficient (2AG 177 ).…”
Section: Sermentioning
confidence: 99%